Condições Atmosféricas Associadas a Eventos de Ressaca no Litoral Sul e do Sudeste do Brasil durante o El Niño 2015/2016 - Machado, Jeferson Prietsch; Miranda, Gustavo Santos Barbosa [UNESP]; Gozzo, Luiz Felippe [UNESP]; Custódio, Maria De Souza [UNESP] (Sociedade Brasileira de Meteorologia, 2020)
The weather systems that cause storms accompanied by strong winds, such as cold fronts and extratropical and subtropical cyclones, often interfere with the sea condition. As a consequence, sea levels can rise dramatically causing coastal flooding. The 2015 and 2016 years were characterized by the occurrence of the positive phase of the phenomenon El Niño - Southern Oscillation, with very strong intensity. The Southern Brazil presented greater conditions of atmospheric instability, with frequent passages of frontal systems and formation of extratropical cyclones, interfering in the sea conditions. In view of the above, this study aimed to evaluate the atmospheric conditions during rough sea events in the South and Southeast of Brazil during 2015/2016 El Niño, through information presented in the Warnings of Bad Weather, issued by the Hydrographic Center of the Brazilian Navy. Through these warnings and ERA-Interim reanalysis data, we analyzed the distributions by sea area, by month and by season of the year, as well as the analysis of synoptic fields plotted on the surface for the 12 most prominent events. As a result, the autumn and winter months recorded the highest occurrences of rough sea in both areas during the 2015/2016 El Niño. In general, four atmospheric patterns favorable to rough sea events were identified, due to the action of extratropical cyclones and the performance of post-frontal high pressure systems.

Os sistemas meteorológicos que ocasionam tempestades acompanhadas de ventos fortes, como frentes frias e ciclones extratropicais e subtropicais, muitas vezes interferem na condição de agitação do mar. Como consequência, o nível do mar pode se elevar extraordinariamente causando inundações na costa. Os anos de 2015 e 2016 foram caracterizados pela ocorrência da fase positiva do fenômeno El Niño - Oscilação Sul, com intensidade muito forte. O Sul do Brasil apresentou maiores condições de instabilidade atmosférica, com frequentes passagens de sistemas frontais e formação de ciclones extratropicais, interferindo nas condições de mar do litoral Sul e do Sudeste do Brasil. Diante do exposto, este estudo objetivou avaliar as condições atmosféricas durante eventos de ressaca no litoral Sul e do Sudeste do Brasil durante o El Niño 2015/2016, através de informações presentes nos Avisos de Mau Tempo, emitidos pelo Centro de Hidrografia da Marinha do Brasil. Por meio desses avisos e dos dados de reanálise do ERA-Interim, foram analisadas as distribuições por área marítima, por mês e por estação do ano, bem como foi realizada a análise de campos sinóticos plotados em superfície para os 12 eventos de maior destaque. Como resultados, os meses de outono e de inverno registraram as maiores ocorrências de ressaca em ambas as áreas, durante o período do El Niño 2015/2016. De um modo geral, quatro padrões atmosféricos favoráveis aos eventos de ressaca foram identificados, em função da atuação de ciclones extratropicais e a atuação de sistemas de alta pressão pós-frontal.
Atmospheric Conditions Associated to Rough Sea Events in the South And Southeastern Coast of Brazil During 2015/2016 El Niño
Keywords: El Niño; rough sea; atmospheric systems; El Niño; Ressaca; sistemas atmosféricos